Agripreneurs' experiences, challenges and prospects toward productivity - Pascua, Rosemarie J. (Saint Louis College : [s.n.], 2021)
This transcendental phenomenological research entitled: "Agribusiness Experiences, Challenges, and Prospects Toward Productivity" assessed the management practices of the agribusiness owners in the Province of Ilocos Sur. The questions focused on these concept/layer of human experience.: management practices, challenges/problems encountered, and industry development. The thematic analysis was employed to interpret the findings of the engagement, management systems, internal factors, external factors, additional government support, and agribusiness environment improvement initiatives. The theme of entrepreneurial engagement embodies the following sub-themes: entrepreneurial mindset, and felt need/need. The theme management systems reveal the practices of the agribusiness in its operation on organization and human resource management, marketing management, operations management, and financial management. The themes on internal and external factors, which includes the different challenges or problems met by the agribusiness which affect its operations. On the theme of additional government support, it includes the support given by the government and other agencies. The theme agribusiness environment improvement initiatives comprise the sub-themes on the different needs of the agribusiness industry for government initiative. The functional relationship of these themes and sub-themes is demonstrated in the Thematic Mode on Sustainable Agribusiness, geared towards the improved performance of agribusiness in Ilocos Sur.
References: pages 123-128.
CHED-La Union
Keywords: Agribusiness